CEO Overconfidence, Digital Transformation, and Strategic Risk-Taking: The Implication on Enterprise Performance at PT Hartadinata Abadi Tbk. - Adinugroho, Muhammad Bayu (Maliki Interdisciplinary Journal, 2025)
The relationship between overconfidence, digital transformation, and strategic risk-taking is becoming increasingly relevant to be studied in depth in the context of improving company performance. This study aims to examine the effect of CEO overconfidence, digital transformation, and strategic risk-taking on company performance. The study uses a quantitative explanatory approach with the object of study being PT Hartadinata Abadi Tbk (HRTA), a public company in the gold jewelry industry listed on the Indonesia Stock Exchange. The data used are secondary data obtained from the company's annual report and financial report for the period 2020–2024, which are officially published through the company's website and the Indonesia Stock Exchange. The variables in this study are operationalized based on empirical standards from previous literature, with indicators covering investment structure, technology spending, leverage level, and financial performance through ROA, ROE, and revenue growth. The results of this study are expected to provide a more comprehensive understanding of the contribution of each variable to company performance, especially in the context of companies operating in the jewelry manufacturing sector